2019
DOI: 10.36380/jwpr.2019.0
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Fungal Fermented Cassava Pulp as a Cheap Alternative Feedstuff in Poultry Ration

Abstract: In order to reduce the production cost, cassava pulp has been incorporated in chicken diets as an energy source. However, the use of such agro-industrial by-product may be confined by its higher fibre and lower protein contents. Improving the nutritional characteristics (lowering fibre and increasing protein content) through fungal solid state fermentation may be conducted to increase the inclusion level of cassava pulp in chicken rations. Apart from an energy source, fungal fermented cassava pulp (FCP) may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Attempts have been conducted to partly reduce the proportion of corn in broiler diets. The use of agro-industrial by-products such as cassava pulp as the alternative energy source for broilers seems to be profitable, but the inclusion of the by-products into broiler diets is often limited by their high and low contents of fibre and protein, respectively (Khempaka et al, 2009;Sugiharto, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts have been conducted to partly reduce the proportion of corn in broiler diets. The use of agro-industrial by-products such as cassava pulp as the alternative energy source for broilers seems to be profitable, but the inclusion of the by-products into broiler diets is often limited by their high and low contents of fibre and protein, respectively (Khempaka et al, 2009;Sugiharto, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation could be a conventional method to improve the nutritional properties and thus increase the incorporation levels of the agroindustrial by-products in broiler diets. Also, supplementation with protein source may compensate the low content of protein in the agroindustrial by-products (Sugiharto, 2019). In this current study, we mixed cassava pulp with Moringa oleifera leaf meal, which is rich in protein (Nkukwana et al, 2015;, prior to fermentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological fermentation by using microbes is a process of the activity of microorganisms or microbes that can produce the product whose texture, flavor, smell and nutrient quality change better than that of the raw material (Mirnawati et al, 2019a;Mirnawati et al, 2019b;Dewi et al, 2019;Mirnawati et al, 2018;Mirrnawati et al, 2017;Adrizal et al, 2017;Mirnawati et al, 2013;Rizal et al, 2013;Rizal et al, 2012;Mirnawati et al, 2012;Aisjah and Abun, 2012;and Mirnawati et al, 2010). According to Sugiharto (2019), solid-fermentation using fungi could be a simple method to improve the nutrient qualities of cassava pulp and thus increased the production of such a cheap agro-industrial by-product in chicken rations. According to Han et al (2003), Rhizopus oligosporus produced protease, lipase, alpha-amylase, glutaminase, and alpha-galactosidase and (Dewi, 2015) found that Rhizopus oligosporus also produces cellulase.…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation is a process of microorganism or microbial activity that can produce a product whose texture, taste, aroma, and nutritional quality changes better than the raw material and result in an increase in the quality and nutritional content of feed ingredients (Aisjah and Abun, 2012;Mirnawati et al, 2019a). Fermentation of cassava waste has been carried out by many researchers, including Sugiharto (2019), who performed a solid-fermentation with fungi which was a simple method to improve the nutrient qualities of cassava pulp and thus increased the production of such a cheap agroindustrial by-product in chicken rations. Therefore, microbes were needed to overcome all of the problems of CLM as a feed ingredient.…”
Section: Introductionmentioning
confidence: 99%